2003
DOI: 10.1016/s0378-7753(03)00087-9
|View full text |Cite
|
Sign up to set email alerts
|

Titanium sinter as gas diffusion backing in PEMFC

Abstract: The use of a titanium sinter material as gas diffusion backing (GDB) in a polymer electrolyte membrane fuel cell (PEMFC) has been evaluated. The study focused on reducing the high contact resistance between the sinter and MEA using platinum and carbon coatings evaporated on the surface of the sinter. The results show that the titanium sinters are a promising solution for gas diffusion backing in a fuel cell and that the initially high contact resistance observed can be effectively reduced with platinum coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Few attempts have been made using metallic thin film as GDM by Fushinobu et al [47], with micromachined titanium film as GDM due to its high endurance property. A similar sort of experiment was also performed by Hottinen et al [48] using titanium sinter material and their investigation illustrated the applicability of titanium sinter as a GDM in free-breathing PEM fuel cells. Micromachined silicon has also been used as GDM for microPEM fuel cell applications tested with hydrogen/air [49].…”
Section: Novel Gas Diffusion Mediummentioning
confidence: 52%
See 1 more Smart Citation
“…Few attempts have been made using metallic thin film as GDM by Fushinobu et al [47], with micromachined titanium film as GDM due to its high endurance property. A similar sort of experiment was also performed by Hottinen et al [48] using titanium sinter material and their investigation illustrated the applicability of titanium sinter as a GDM in free-breathing PEM fuel cells. Micromachined silicon has also been used as GDM for microPEM fuel cell applications tested with hydrogen/air [49].…”
Section: Novel Gas Diffusion Mediummentioning
confidence: 52%
“…From the various studies in open literature [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], it is observed that though carbon cloth and carbon paper have their own pros and cons, carbon paper has been recommended by most of the authors especially for low humidity operation and carbon cloth for high humidity operation. The worst performance of the carbon cloth is likely to be attributed to contact resistances; however, at high current density, carbon papers have some issues pertaining to water management.…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…Second, both Ti and Ti non-stoichiometric oxides possess high electrical conductivities [25], and finally TiO x is stable against corrosion acting as a protective layer for the underlying metal. Recently much emphasis has been placed on Ti and TiO x materials as backing layers and/or fuel cell supports [26,27]. In the future, VACNF layer could be grown on a Ti-based alloy with the second component being a material that can be easily leached out creating porosity required for the PEMFC backing layers.…”
Section: Preparation Of the Working Electrodesmentioning
confidence: 99%
“…Hottinen et al [15] evaluated the applicability of titanium sinter material as gas diffusion backing in PEMFC. The results showed that the titanium sinters were a promising solution for gas diffusion backing in a fuel cell and that the initially high contact resistance observed could be effectively reduced with platinum coating.…”
Section: Introductionmentioning
confidence: 99%